2011
DOI: 10.1021/jz1016526
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of the Mechanisms of Superoxide-Induced Decomposition of Organic Carbonate-Based Electrolytes

Abstract: There is increasing experimental evidence that organic carbonate-based electrolytes are incompatible with the discharge products of the nonaqueous lithium−air (oxygen) battery. Theoretically, the lithium−air battery offers the highest gravimetric density for energy storage applications, promising to revolutionize electric vehicle transportation. Calculations suggest that propylene carbonate, ethylene carbonate, and dimethyl carbonate, commonly used electrolytes in Li-ion batteries, are easily decomposed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
191
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(200 citation statements)
references
References 36 publications
8
191
0
1
Order By: Relevance
“…For example, the carbonate based solvents, commonly used in Li-ion batteries, 13 were not appropriate for Li-O 2 batteries because of their susceptibility to nucleophilic attack by reduced O 2 − species. 10,[14][15][16][17] Li-O 2 batteries usually consist of a lithium foil anode, a lithium salt dissolved in an organic solvent as electrolyte and a porous carbonbased cathode. During the discharge metallic lithium anode releases lithium ions (Li + ) to the electrolyte, while electrons are transported to the cathode through an external circuit.…”
mentioning
confidence: 99%
“…For example, the carbonate based solvents, commonly used in Li-ion batteries, 13 were not appropriate for Li-O 2 batteries because of their susceptibility to nucleophilic attack by reduced O 2 − species. 10,[14][15][16][17] Li-O 2 batteries usually consist of a lithium foil anode, a lithium salt dissolved in an organic solvent as electrolyte and a porous carbonbased cathode. During the discharge metallic lithium anode releases lithium ions (Li + ) to the electrolyte, while electrons are transported to the cathode through an external circuit.…”
mentioning
confidence: 99%
“…For both cases, the specific capacities are much smaller than those of nanostructured electrodes due to the reduction of surface area. Figure 6b shows the plateau discharge voltage as a function of nanostructure spacing of S = 4, 8,12,16,20,26,30, and 36 nm, where the discharge voltage monotonically increases from 2.636 V for S = 4 nm to 2.647 V for S = 36 nm. The results also show two different slopes for the plateau cell voltage versus nanostructure spacing curve.…”
Section: Resultsmentioning
confidence: 99%
“…However, the relatively new Li-air battery still underperforms in several key factors when compared to the more established Li-ion battery, such as low round trip efficiency (70% 9,12 vs. >95% 13 ), low drawing current density (0.1-1.0 mA cm −28,14 vs. 30 mA cm −214 ) and poor cycle life (∼100 15,16 vs. 5000 17 ). The source of these problems can be traced to a number of key issues, including the electric insulation of the reaction products, [18][19][20][21][22] parasitic irreversible side reactions, [23][24][25][26] electrolyte instability, 12,23,24 and electrode degradation. 12,27 These shortcomings must be overcome in order for the Li-air battery to become viable.…”
mentioning
confidence: 99%
“…It was found that PC is susceptible to the attack of superoxide radical (O 2 − ) based on Density Functional theory (DFT) study and coupled-cluster calculations by Bryantsev and Blanco as shown in Fig. 10.3 [ 45 ]. Subsequent reactions lead to decomposition to form carbonate species as discharge products.…”
Section: Organic Carbonate Solvents: Lessons Learnedmentioning
confidence: 99%